(untitled) (Research, Society and Development, 2022)
Bisphosphonates (BFs), such as alendronate, risedronate, ibandronate, and clodronate, are potent osteoclast-inhibiting drugs and are considered the first-choice therapy in diseases that affect bone metabolism. A significant adverse effect seen in patients using oral or intravenous BPs who have undergone invasive dental procedures such as implant therapy is bisphosphonate-related osteonecrosis of the jaw (OMRB), which is clinically characterized by painful exposure of bone in the maxillofacial region. In this sense, this study aims to review the literature on the protocol in dento-alveolar surgeries in patients using bisphosphonates, as well as to describe the clinical manifestations of drug-related mandibular osteonecrosis. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were covered between the years 2010 to 2022. Osteonecrosis of the jaws caused by bisphosphonates is an uncommon, but potentially very serious, adverse consequence of drug therapy for BP. It is mainly associated with the use of more potent amino-bisphosphonates for long periods of time. The most common antecedent event to the development of clinical lesions is invasive dental treatment, and it is therefore particularly important that oral health professionals have an understanding of their causes and management. Prevention remains the most important aspect of management and begins at the time of first prescription and should continue for the rest of the patient’s life because of the lasting effect of these drugs on bone.